Factors related quality of life among people living with HIV and AIDS in Bulukumba - Suswani, Andi; Arsin, A. Arsunan; Amiruddin, Ridwan; Syafar, Muhammad; Palutturi, Sukri (International Journal Of Community Medicine And Public Health, 2018)
Background: Good quality of life is a condition that must be achieved and maintained by PLHIVs. This study aims to identify factors related to the quality of life among people living with HIV (PLHIV) in the Bulukumba district. Methods: Cross sectional study was conducted among 42 PLHIV. The samples were selected by using purposive sampling technique which was conducted for 30 days. Data was collected by using WHOQOL-HIV BREF and analyzed by logistic regression to identified factors related quality of life. Results: Most (52.4%) of PLHIV have not good quality of life. Bivariate analysis showed that behavior (p=0.0293), ARV access (p=0.0197) and adherence (p=0.0088) were factors that increased quality of life among PLHIV. Adherence variable was the greatest influence to the quality of life with OR 11.06 with CI 95% 1.22-100.38. Conclusions:Behavior, ARV access easily, and treatment adherence were factors that influence quality of life among PLHIV. Improving behavior, access ARV, and adherence are recommended to maintain quality of life.